Sustainable Development Goals: New targets hold promise for Africa - Tim Wall (Africa Renewal, 2014)
The first draft of the world’s new development agenda – the Sustainable Development Goals – takes into account Africa’s interests, but not in the same way as the expiring Millennium Development Goals (MDGs) once did.